Adaptation of the five-factor BFI-10 personality screening questionnaire and testing of its diagnostic properties on the example of drug users (Law and Safety, 2021)
Extended annotation. The large number of questions from the most common and cited in the scientific literature questionnaires of the "Big Five" makes them unsuitable for surveys of large samples of poorly motivated respondents. It is described the process of adaptation, validation and diagnostic properties of the five-factor BFI-10 Express Diagnostic Screening Questionnaire, which contains only 10 questions and has shown high reliability in large comparative cross-cultural studies using a web methodology. Validation was performed by filling in parallel forms of the 5PFQ questionnaire for 75 questions (validated version of A.B. Khromov, N = 2492), LBP questionnaire for 25 questions (validated version of L.F. Burlachuk and D.K. Korolev, N = 246) and questionnaire BFI-10. The validation of the BFI-10 has showed that our adapted version of the questionnaire measured the same constructs as the 5PFQ and BFL questionnaires. There is a positive correlation between the total values of the scales of all three questionnaires of the "big five", significant at the level of p
Keywords: screening; personality; big five; adaptation; construct validity; reliability; BFI-10.